2005
DOI: 10.1007/s00228-004-0886-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 enzyme-mediated drug metabolism at exposure to acute hypoxia (corresponding to an altitude of 4,500�m)

Abstract: Acute hypoxia corresponding to hypoxia at altitudes of 4,500 m does not impair the metabolism mediated by CYP1A2 or CYP3A4. At rapid ascent to and short-term stay at altitudes up to 4,500 m, the doses of drugs metabolized by these CYPs do therefore not require dose modification, and major changes in the disposition of already administered drugs are not to be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…[ 26 ] In animal experiments, CYP1A1 and CYP1A2 protein expression was decreased in the liver after 24 h of hypoxic exposure, whereas expression of the CYP3A6 protein was increased. [ 18 ] Although the effects of hypoxemia on the expression of CYPs depend on the cell type, IH obviously causes a general decrease in the expression levels in the liver,[ 24 ] which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[ 26 ] In animal experiments, CYP1A1 and CYP1A2 protein expression was decreased in the liver after 24 h of hypoxic exposure, whereas expression of the CYP3A6 protein was increased. [ 18 ] Although the effects of hypoxemia on the expression of CYPs depend on the cell type, IH obviously causes a general decrease in the expression levels in the liver,[ 24 ] which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Although there is no clear explanation as to the exact mechanism of how IH influences CYP expression, it has been reported that inflammatory factors may have an influence on the transcription of CYPs. [ 18 ] As shown in our study, the increased expression of IL-1β may inhibit the transcription of CYPs and cause a decrease in their expression.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These small changes in the activity of CYP2D6 and CYP3A4 suggest that acute hypoxia has no clinically signifi cant effects on CYP enzymes in humans. Another study confi rms this, examining the effect of acute hypoxia on CYP1A2 (theophylline metabolism) and CYP3A4 (verapamil) in 20 subjects in a normobaric hypoxic chamber [ 57 ]. Subjects were randomly allocated to receive intravenous infusions of theophylline (6 mg/kg) or verapamil (5 mg) in a crossover design, with exposure to normoxia and hypoxia (12 % oxygen) corresponding to the ambient PaO 2 at 4,500 m. Acute hypoxia did not alter the pharmacokinetics of theophylline ( T 1/2 ± SD: 9.29 ± 1.77 vs. 9.39 ± 1.40 (hypoxia)), verapamil (2.00 ± 0.98 vs. 1.79 + 0.58), or their principal metabolites .…”
Section: Hepatic Functionmentioning
confidence: 95%
“…However, animal studies measuring the effect of hypoxia on the activity or levels of P450 enzymes in the liver have yielded conflicting results. Some studies have shown that hypoxia did not impair the metabolism mediated by cytochrome P450 [8,9]. …”
Section: Introductionmentioning
confidence: 99%